THE NEED FOR CARGO INSURANCE AND THE MECHANISM OF USING INCOTERMS AND INSURANCE CONTRACTS - Shoymardonova Mushtariybegim Alisher kizi (Лучшие интеллектуальные исследования, 2024)
Annotation. In this article the requirement of cargo insurance contracts in people’s lives in order to conduct business has been discussed, additionally, Incoterms and cargo insurance contracts have been compared with each other.